(untitled) (Rajshahi University Journal of Science and Engineering, 2016)
The purpose of this study is to understand the electrochemical corrosion behavior of 1wt% Cu content Al-6Si-0.5Mg alloy in 0.1M NaCl solution. The potentiodynamic polarization curves reveal that 1wt% Cu content alloy is less prone to corrosion than the Cu free alloy. The EIS test results show that corrosion resistance or polarization resistance (Rct) increases with the addition of 1wt% Cu to Al-6Si-0.5Mg alloy. Higher polarization resistance (Rp) has been obtained with the addition of 1wt% Cu to the Al-6Si-0.5Mg alloy. Due to addition of Cu and thermal modification, the magnitude of open circuit potential (OCP), corrosion potential (Ecorr) and pitting corrosion potential (Epit) of Al-6Si-0.5Mg alloy in NaCl solution were shifted to the more noble direction.